2007
DOI: 10.1073/pnas.0611448104
|View full text |Cite
|
Sign up to set email alerts
|

A monomeric G protein-coupled receptor isolated in a high-density lipoprotein particle efficiently activates its G protein

Abstract: G protein-coupled receptors (GPCRs) respond to a diverse array of ligands, mediating cellular responses to hormones and neurotransmitters, as well as the senses of smell and taste. The structures of the GPCR rhodopsin and several G proteins have been determined by x-ray crystallography, yet the organization of the signaling complex between GPCRs and G proteins is poorly understood. The observations that some GPCRs are obligate heterodimers, and that many GPCRs form both homo-and heterodimers, has led to specul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

27
554
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 618 publications
(589 citation statements)
references
References 46 publications
27
554
0
Order By: Relevance
“…Nonetheless, the mutant TPs that reached the plasma membrane bound the antagonist [ 3 H]-SQ29,548 with normal affinity, and could be activated by the stable TXA 2 agonist U46619 as efficiently as the wild-type receptors at equal level of expression. These data are consistent with the observation that monomeric GPCRs are the minimal functional unit in G protein activation and that dimerization/oligomerization is not absolutely required for this process [9][10][11][12][13][14]43]. However, the U46619 agonist, stimulated TM1 mutant TPa and TPb with a marked reduction in potency, thus suggesting that dimer formation favors a more efficient signaling complex.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Nonetheless, the mutant TPs that reached the plasma membrane bound the antagonist [ 3 H]-SQ29,548 with normal affinity, and could be activated by the stable TXA 2 agonist U46619 as efficiently as the wild-type receptors at equal level of expression. These data are consistent with the observation that monomeric GPCRs are the minimal functional unit in G protein activation and that dimerization/oligomerization is not absolutely required for this process [9][10][11][12][13][14]43]. However, the U46619 agonist, stimulated TM1 mutant TPa and TPb with a marked reduction in potency, thus suggesting that dimer formation favors a more efficient signaling complex.…”
Section: Discussionsupporting
confidence: 90%
“…In spite of the evidence that rhodopsin and the b 2 -adrenergic receptor (b2-AR) activate their cognate G protein in the monomeric form [9][10][11][12] and that supramolecular organizations of rhodopsin [9], neurotensin 1 receptor [13] and leukotriene B 4 receptor (BLT 2 ) [14] reduce G protein coupling, formation of GPCR oligomers in living cells has been widely demonstrated [15][16][17]. Indeed, it was recently inferred that the b 2 -AR exists in dynamic equilibrium between monomeric and higher-order oligomers, with the average size of the oligomer being a tetramer and with inverse agonists promoting higher order oligomerization [15].…”
Section: Introductionmentioning
confidence: 99%
“…they are not in equilibrium and they cannot be converted into each other. This is possible in artificial sytems such as that described by Whorton et al, [3] but there is evidence that it is not likely to happen in cells.…”
Section: Introductionmentioning
confidence: 99%
“…␤ 2 AR requires a lipid bilayer to efficiently couple to Gs. Whorton et al recently showed that purified ␤ 2 AR can be reconstituted into recombinant HDL particles (rHDL) as monomers, and that monomeric ␤ 2 AR couples efficiently to Gs (31). Thus, mB-␤ 2 AR was reconstituted into rHDL, and the response to the agonist isoproterenol (ISO) was determined.…”
Section: Agonist-and Gs-induced Changes In Mb-␤2ar Reconstituted Intomentioning
confidence: 99%